The board structure and firm performance in SMEs: Evidence from Spain - Blanca Arosa; Txomin Iturralde; Amaia Maseda (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
The aim is to analyse the efficiency of the board of directors as a corporate governance mechanism. For this purpose, we examine the effect of board composition, size, activity, leadership structure and CEO tenure on firm performance. To test our hypothesis we use a sample of 307 Spanish SMEs, none of which is listed. Our main empirical result is the negative impact of the outside directors proportion and board size on firm performance. The presence of outside directors can be said not to have resulted in improved firm performance. Despite the greater monitoring, advising and networking capacity attributed to outside directors, the firms in the sample showed a significant presence of insider directors, an aspect that may be related to their greater knowledge of the firm, with a subsequently positive effect on strategic planning decisions. The negative effect of board size could indicate that the disadvantages of worse coordination, flexibility and communication inside large boards seem to be more important than the benefits of better manager control by the board of directors.
Keywords: G3; 330; Board composition; Board size; SME; Duality; CEO tenure